Stylopine: A potential natural metabolite to block vascular endothelial growth factor receptor 2 (VEGFR2) in osteosarcoma therapy - Velayutham, Naveen Kumar; Thamaraikani, Tamilanban; Wahab, Shadma; Khalid, Mohammad; Ramachawolran, Gobinath; Abullais, Shahabe Saquib; Wong, Ling Shing; Sekar, Mahendran; Gan, Siew Hua; Ebenezer, Angel Jemima; Ravikumar, Mrinalini; Subramaniyan, Vetriselvan; et al. (Frontiers in Pharmacology, 2023)
Vascular endothelial growth factor (VEGF) signals cell survival, cell migration, osteogenesis, cell proliferation, angiogenesis, and vascular permeability by binding to VEGF receptor 2 (VEGFR-2). Osteosarcoma is the most common primary bone cancer, majorly affects young adults. Activation of VEGFR-2 signaling is a therapeutic target for osteosarcoma. The present study aimed to evaluate the potency of stylopine in regulation of the VEGFR-2 signaling pathway and its anti-tumour effect human MG-63 osteosarcoma cells. The in-silico study on benzylisoquinoline alkaloids was carried out for analyzing and shortlisting of compounds using a virtual screening, Lipinski’s rule, bioavailability graphical RADAR plot, pharmacokinetics, toxicity, and molecular docking studies. Among the benzylisoquinoline alkaloids, stylopine was selected and subjected to in-vitro studies against human MG-63 osteosarcoma cells. Various experiments such as MTT assay, EtBr/AO staining, mitochondrial membrane potential assessment, transwell migration assay, gene expression analysis by a quantitative real time polymerase chain reaction (qRT-PCR) method, SDS-PAGE followed by immunoblotting were performed to evaluate its anti-tumour effect as compared to standard axitinib. The MTT assay indicates that stylopine inhibits cell proliferation in MG-63 cells. Similarly, as confirmed by the EtBr/Ao staining method, the MMP assay indicates that stylopine induces mitochondrial membrane damage and apoptosis as compared to axitinib. Moreover, stylopine inhibits the VEGF-165 induced MG-63 cell migration by a trans-well migration assay. The immunoblotting and qRT-PCR analysis showed that stylopine inhibits the VEGF-165 induced VEGFR2 expression in MG-63 cells. It is concluded that stylopine has potential to regulate VEGFR2 and can inhibit osteosarcoma cells to offer a new drug candidate for the treatment of bone cancer in future.